A histological investigation of the occurrence of non‐reproductive female bluefin tuna Thunnus thynnus in the Mediterranean Sea - R. Zupa; A. Corriero; M. Deflorio; N. Santamaria; D. Spedicato; C. Marano; M. Losurdo; C. R. Bridges; G. De Metrio (Journal of Fish Biology, 2009)
The presence of non‐reproductive Atlantic bluefin tuna Thunnus thynnus females in the Mediterranean Sea was investigated through histological analysis of the gonads. Three hundred and twenty‐six ovary samples were collected from adults captured at different locations in the Mediterranean Sea during the reproductive seasons between 1998 and 2008. Only three specimens were considered to be in a non‐reproductive state: two of them were in a reabsorbing state showing ovaries with early vitellogenic oocytes and extensive α and β atresia of vitellogenic follicles; the third showed gonads with perinucleolar oocytes and was considered to be in a resting state. The low occurrence of non‐reproductive individuals found in this study makes it unlikely that non‐reproductive individuals aggregate with reproductive ones during their migration towards spawning grounds. Further research is suggested in order to investigate the potential presence of non‐reproductive individuals on non‐spawning grounds during the reproductive season.

Germ cell proliferation and apoptosis during different phases of swordfish ( Xiphias gladius L.) spermatogenetic cycle - A. Corriero; S. Desantis; C. R. Bridges; D. E. Kime; P. Megalofonou; N. Santamaria; F. Cirillo; G. Ventriglia; A. Di Summa; M. Deflorio; F. Campobasso; G. De Metrio (Journal of Fish Biology, 2007)
Seasonal changes of testicular activity of the swordfish Xiphias gladius and correlations of plasma levels of testosterone (T) and 11‐ketotestosterone (11‐KT) with proliferation and apoptosis of germ cells, determined, respectively, with monoclonal antibodies against proliferating cell nuclear antigen and terminal deoxynucleotidyl transferase‐mediated d’UTP nick end labelling, are described. Three phases of the reproductive cycle were found: active spermatogenic (May), spawning (June to July) and spent (August to September) stages. Germ cell proliferating activity was highest in May, decreased during June to July and remained stable during August to September. Apoptotic germ cells, primary spermatocytes and spermatogonia, were present in all the specimens analysed and were more abundant in May. The levels of 11‐KT in plasma were always higher than T and were highest in May, in concomitance with the maximum proliferation and apoptosis rate of germ cells.

Resistance of parenchyma cells in wood to degradation by brown rot fungi - F. W. M. R. Schwarze; S. Fink; G. Deflorio (Mycological Progress, 2003)

Histological investigation on the ovarian cycle of the bluefin tuna in the western and central Mediterranean - A. Corriero; S. Desantis; M. Deflorio; F. Acone; C. R. Bridges; J. M. De la Serna; P. Megalofonou; G. De Metrio (Journal of Fish Biology, 2003)
The histological analysis of eastern Atlantic bluefin tuna Thunnus thynnus ovaries caught from February to September 1999–2000, made it possible to distinguish the presence of seven oocyte developmental stages and allowed the characterization of six time‐dependent ovary maturity stages. The ovaries of mature (fork length, L F ≥ 110 cm) bluefin tuna were non‐active from August (spent period) to March (quiescent period) when they contained only perinucleolar‐stage oocytes. Ovary development started in April to early May (recrudescent period) with the appearance of oocytes at the lipid stage. Vitellogenesis appeared in mid‐May (ripening period) and post‐vitellogenesis occurred in late May to mid‐June (pre‐spawning period). In late June to early July, hydrated oocytes, a sign of imminent spawning, were found only in specimens caught in Balearic waters. Females ranging between 100 and 110 cm L F , captured during the recrudescent and ripening periods, had the largest oocytes at the lipid stage, most of which were degenerating. An extensive vitellogenic atresia was observed in the ovaries of five females caught during the spawning period in non‐spawning areas.